Morphophysiological responses of cowpea to irrigation with saline water and application of bovine biofertilizer - Veras, Mario Leno Martins; Melo Filho, José Sebastião de; Alves, Lunara de Sousa; Souza, Leandra de Melo Cavalcante; Dias, Thiago Jardelino (Comunicata Scientiae, 2018)
Cowpea crop has great economic importance, mainly in the Northeast, where it is a food source for several families. In this context, the objective was to evaluate the effect of levels of electrical conductivity on irrigation water as a function of the application of biofertilizer in the growth and production of cowpea. The experimental design was completely randomized, presenting a factorial scheme of 4 x 2, corresponding to four levels of electrical conductivity of the irrigation water (ECw), 1; 2; 3 and 4 dS m-1 and the presence and absence of bovine biofertilizer application in four replicates. Plant height, number of leaves, stem diameter, number of lateral branches, main branch length, root dry weight, shoot and total number, pod number per plant, mass dry weight of the pod, the length and mean diameter of the pod, the number of grains per plant, the number of grains per pod, the mass of grains and the mass of 100 grains. The increase of ECw inhibits vegetative and productive growth of cowpea and the use of enriched bovine biofertilizer attenuates the effects of saline stress on cowpea, favoring its development.